Public Service During the Jokowi Administration: An Examination of High-Quality Services Delivery 2014 to 2016 - Praditya, Editha; Maarif, Syamsul; Ali, Yusuf; Saragih, Herlina Juni Risma; Sutanto; Duarte, Rui; Suprapto, Firre An (Universitas Negeri Surabaya, 2024)
The Government is entrusted with two fundamental tasks: crafting superior public policies and delivering public services of the utmost quality. The hallmark of a successful President lies in their ability to ensure that public services rendered under their administration are of impeccable quality. This study, spanning the years 2014 to 2016, employed a quasi-qualitative methodology. The findings revealed that public services during the Jokowi era did not meet the anticipated standards of quality. Consequently, this research proposes five strategic priorities for the future. First and foremost, it is imperative not merely to concentrate on public service provision but to spearhead a concerted effort towards establishing a pervasive culture of high-quality public services. Secondly, there is a pressing need to refine existing policies related to the development of public services, including assessment methodologies. Current policies are reflective of the developmental paradigm typical of emerging nations, characterized by a mindset prevalent in developing countries, particularly in Indonesia. Thirdly, there is a crucial need to elevate performance criteria from mere basic indicators to intermediate metrics that offer substantial value addition. Moreover, striving towards an 'advanced' level of service provision, one that is innovative and creates inherent value, is paramount. Fourthly, it is essential for the bureaucracy to shift its focus from mere reporting of service outcomes to a heightened emphasis on the functional aspects of service delivery. Lastly, fostering a collective public consciousness is pivotal. Public services ought to be perceived as a benevolent endowment from the Government to its citizens, surpassing the realm of rights and duties. This awareness is foundational to nurturing a society where public services are not just a transactional obligation but a cherished privilege bestowed upon the populace by the Government.